Closing the Gap: Promoting Suspect Communities' Cooperation with Airport Security. Issue 6 (17th August 2020) - Perry, Gali; Hasisi, Badi
ABSTRACT: In the aftermath of 9/11, aviation security has become a central component of counterterrorism. To mitigate threats whilst maintaining flight schedules, airport security officers require the cooperation of all passengers, but especially of ethnic minorities perceived as posing a potential threat to homeland security, often referred to as "suspect communities." Passengers from suspect communities are subject to rigorous screening, but are also regarded as a source of information, making their cooperation even more important than that of other passengers. Nevertheless, suspect communities' cooperation with airport security, and the gap between their attitudes and those of other passengers, have not yet been examined. The current study utilizes a survey of 1970 passengers at the Ben-Gurion airport in Israel, examining passengers' perceptions of airport security and their willingness to cooperate. We find that passengers belonging to the suspect community of Israeli Muslims were less willing to cooperate with security procedures than all other passengers. However, when controlling for passengers' perceptions of legitimacy and procedural justice, Israeli Muslims were more willing to cooperate with airport security than Israeli Jews. The findings highlight the importance of legitimacy and procedural justice perceptions in obtaining the cooperation of suspect communities, and suggest practical pathways for improving cooperation.